2018
DOI: 10.3390/pharmacy6040130
|View full text |Cite
|
Sign up to set email alerts
|

Patient Perceptions of Electronic Prescriptions in Belgium: An Exploratory Policy Analysis

Abstract: In today’s world, digitalization and automation are ubiquitous and different countries have different strategies for implementing information technology in health care. In Belgium, these plans include the dematerialization of prescriptions, following the implementation of a system of electronic prescribing. In the light of these changes, we studied the attitudes of patients toward a paperless prescription. We collected the opinions of 273 patients by survey. Older people, or people with more complex medical ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…It is worth noting that a subjective assessment of one’s familiarity with e-prescribing does not necessarily reflect the actual state of knowledge. In a similar study conducted in Belgium, the majority (68, 81%) of people surveyed declared that they knew what e-prescription is [ 23 ]. However, 34% of respondents declared that their physician does not use e-prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that a subjective assessment of one’s familiarity with e-prescribing does not necessarily reflect the actual state of knowledge. In a similar study conducted in Belgium, the majority (68, 81%) of people surveyed declared that they knew what e-prescription is [ 23 ]. However, 34% of respondents declared that their physician does not use e-prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Digitalization and robotization are wherever in the general public, unmistakable in the medicinal services division, wherever there is a huge chance that is obtained. The advantages are speed, reliability, limit, incorporation, and breakdown of data (Suykerbuyk et al, 2018). The progressions in luence the method of solutions is dealt with.…”
Section: Introductionmentioning
confidence: 99%
“…Another study in adults identified between 30% and 50% of testosterone preparations compounded by ten compounding pharmacies were within ±20% of the prescribed dose [6]. One report from Belgium, a country that in January 2019 made eRx mandatory, indicated that patients with more complex medical conditions were more likely to want paper prescriptions [7]. These outcomes demonstrate the risk for error within every step of compounded drug use and pediatric prescriptions in general, from preparation to administration.…”
Section: Introductionmentioning
confidence: 99%